Does Water-Jet Force Affect Cryopreserved Adipose-Derived Stem Cells? Evidence of Improved Cell Viability and Fat Graft Survival. Issue 2 (August 2021) - Qu, Yaping; Luan, Jie; Mu, Dali; Wang, Qian; Li, Zifei; Liu, Tong; Fu, Su
Abstract : Background: Adipose tissue harvested by liposuctions is an available source of adipose-derived stem cells (ASCs). Water-jet–assisted liposuction is a favorable method for fat collection with little mechanical damage. This study aimed to investigate whether or not the water-jet–assisted liposuction made a difference in the biological characteristics of cryopreserved ASCs and fat graft survival in cell-assisted lipotransfer. Methods: Human lipoaspirates were obtained from the abdomen or thighs of 20 female participants for body contouring. A single surgeon randomly harvested 50 mL of adipose tissue by the water-jet–assisted liposuction and the conventional liposuction, respectively. Adipose-derived stem cells were isolated from lipoaspirates and then cryopreserved for 4 weeks. Cryopreserved ASCs were used to examine the surface markers, cell proliferation, migration, and adipogenic differentiation in vitro. The fat survival of ASCs-enriched grafts from different liposuctions was measured in animal models. Results: The cryopreserved ASCs with the water-jet assistance had better capacities of cell proliferation, migration, and adipogenic differentiation and achieved a better survival result of ASCs-enriched fat grafting. Conclusions: Cryopreservation of ASCs with the water-jet force showed more excellent biological characteristics. The water-jet–assisted liposuction was superior to the conventional liposuction in obtaining ASCs and fat survival of coimplantation with grafts. Abstract : Supplemental digital content is available in the text.